Analisis Gaya Belajar Mahasiswa Program Studi Pendidikan Bahasa Indonesia Universitas Katolik Weetebula - Bitu, Yuliana Sesi; Suluh, Melkianus (Lembaga Intelektual Muda (LIM) Maluku, 2024)
The purpose of this study is to describe learning styles and describe solutions in presenting learning in accordance with the learning styles of students of the Indonesian Education Study Program, Weetebula Catholic University. This type of research is survey research with a qualitative descriptive approach. The subject of this study was a student of PBI Study Program, Weetebula Catholic University. The data collection technique used in this study was questionnaire. Based on the results of the study, it was found that students who tended to visual learning style as much as 53.74%, auditorial learning style as much as 29.43%, and kinesthetic learning style as much as 16.83%. The results of these findings show that the most dominant type of learning style of Indonesian Education Study Program students is the visual learning style type. Lecturers in presenting learning the main type of learning used is the visual type of learning. To accommodate the other two learning styles, learning needs to be supported by auditorial and kinesthetic learning types. Research related to learning styles is important. The results of the research can be information for teachers or lecturers in making learning designs that are in accordance with the learning styles of students so that students can absorb the material optimally